2008
DOI: 10.3748/wjg.14.7376
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of celiac disease in Iranian children with idiopathic short stature

Abstract: We conclude that the prevalence of celiac disease is high in patients with ISS and it is important to test all children with ISS for celiac disease by measuring serologic markers and performing an intestinal biopsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 28 publications
1
24
1
Order By: Relevance
“…The prevalence of CD was higher (35-59%) in the studies 11,[14][15][16][17][18] where either the endocrinal workup had been done and/or the sample was very small. In rest of the studies 10,13,[19][20][21][22][23][24] where the endocrinal causes had not been ruled out in the selected children and/or the sample size was relatively larger, the prevalence reported was lower (1.7-8.3%).…”
Section: Discussionmentioning
confidence: 85%
“…The prevalence of CD was higher (35-59%) in the studies 11,[14][15][16][17][18] where either the endocrinal workup had been done and/or the sample was very small. In rest of the studies 10,13,[19][20][21][22][23][24] where the endocrinal causes had not been ruled out in the selected children and/or the sample size was relatively larger, the prevalence reported was lower (1.7-8.3%).…”
Section: Discussionmentioning
confidence: 85%
“…19,20 Although in most of the cases early intervention with gluten free diet enable some catching up growth 21 , the real pathogenesis behind the short height related to CD is still not very clear. 22 …”
Section: Discussionmentioning
confidence: 99%
“…For instance; incidence of CD has been reported as high as 0.01%-0.5% and 1.2% of the total population in Sweden and England, respectively. Rates are higher in Arabian countries, with 0.5%-1.0% of the total population having CD [6,7,8].…”
Section: Iranian Studies On Celiac Diseasementioning
confidence: 99%
“…Sensitivity, specificity and PPV for IgA TTG antibodies were 88.6%, 94.2% and 88.6%, respectively. They concluded that the prevalence of celiac disease is high in patients with ISS and it is important to test all children with ISS for celiac disease by measuring serologic markers and performing an intestinal biopsy [8].…”
Section: Iranian Studies On Celiac Diseasementioning
confidence: 99%
See 1 more Smart Citation